2015
DOI: 10.1039/c5ra01553g
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and controlled drug delivery using a temperature and ultra-violet responsive liposome with excellent breast cancer suppressing ability

Abstract: Drug delivery systems (DDS) with favorable serum stability, high intra-tumor accumulation and tumor specific drug release are highly desired for promoting chemotherapeutic efficacy. However, a more stable DDS means it is more difficult to release its content, and vice versa. In order to resolve this conflict, a Fab conjugated thermo-responsive liposome (FCTRL) based on 1,2-bis(10,12-tricosadiynoyl)sn-glycero-3-phosphocholine (DC8,9PC) and P(IPPAm-co-DMAAm)-b-PLA diblock copolymer (PPDC) was developed in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…An 11.2-fold increase in cellular uptake was achieved by the modification of a liposomal doxorubicin system with an SP5-2 moiety by Chang et al [21] Transferrinmodified nanoparticles demonstrated a six-fold increase in uptake versus control liposomes for a breast cancer cell line [22]. Similarly, several other actively targeted therapies have been developed to deal, specifically, with breast cancer using various targeting ligands including transferrin [23,24], estrogen [25], tamoxifen [26], folic acid [27], RGD peptide [28,29] and many others [30][31][32][33], yielding similar success to the previously outlined articles.…”
Section: Structure Of Nanocarriersmentioning
confidence: 99%
“…An 11.2-fold increase in cellular uptake was achieved by the modification of a liposomal doxorubicin system with an SP5-2 moiety by Chang et al [21] Transferrinmodified nanoparticles demonstrated a six-fold increase in uptake versus control liposomes for a breast cancer cell line [22]. Similarly, several other actively targeted therapies have been developed to deal, specifically, with breast cancer using various targeting ligands including transferrin [23,24], estrogen [25], tamoxifen [26], folic acid [27], RGD peptide [28,29] and many others [30][31][32][33], yielding similar success to the previously outlined articles.…”
Section: Structure Of Nanocarriersmentioning
confidence: 99%
“…AZD-2014-loaded NPs and rituximab-conjugated NPs were prepared by use of a nanoprecipitation method [21]. PLGA-PEG or Ab-PLGA-PEG ($90 mg) and AZD-2014 (10 mg) were dissolved in 10 ml dimethyl sulfoxide, then slowly added dropwise with stirring at 2500 rpm to 30 ml deionized water for 30 min.…”
Section: Fabrication Of Nanoparticlesmentioning
confidence: 99%
“…Considering that intravenous administration was planned, NP stability in serum should be known. For approximation of this value, we used Ab-NPs-AZD-2014 and NPs-AZD-2014 in 50% bovine serum albumin (BSA) in Dulbecco's modified Eagle Medium [21]. After incubation at 37 C for various times, size distribution NPs-albumin was measured with dynamic light scattering (DLS).…”
Section: Nanoparticle Stabilitymentioning
confidence: 99%
“…Several reasons may help explain the compromised clinical efficacy of ADCs: (i) premature deconjugation or degradation of ADCs in circulating blood due to linker instability; (ii) inadequate intracellular uptake by tumor cells due to rare target internalization of antibody–antigen complex; (iii) slow and deficient drug release inside tumor cells due to the gradual biodegradation behavior of linkers . However, it seems that more stable of an ADC product means more difficult to release its cytotoxicity agents inside tumor cells, and vice versa . The contradiction between linker stability and drug release remains a key point to resolve for enhanced tumor suppressing activities .…”
Section: Introductionmentioning
confidence: 99%
“…However, it seems that more stable of an ADC product means more difficult to release its cytotoxicity agents inside tumor cells, and vice versa . The contradiction between linker stability and drug release remains a key point to resolve for enhanced tumor suppressing activities . In addition, how to improve the tumor cell endocytosis of ADC products remains another important challenge …”
Section: Introductionmentioning
confidence: 99%